Features of the course and treatment of JIA-associated uveitis (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To investigate the features of the clinical course of and the state of eye care for patients with juvenile idiopathic arthritis (JIA)-associated uveitis (JIA-U).Materials and Methods: We analyzed the results of monitoring 121 patients aged 7 to 18 years with JIA. Twenty one (17.35%) of these had uveitis.Results: In 17 (80.95%) of the examined JIA-U patients, JIA onset age was younger than 6 years, and mean JIA onset age was significantly younger than in JIA patients without uveitis (2.89±0.26 years vs 6.43±0.4 years, р
Keywords: uveitis; juvenile idiopathic arthritis